Improving Indonesian Senior High School Students’ Critical Thinking Skill through Science Integrated Learning (SIL) Model - Nuri, Ayu Rahma Ulufa; Sajidan, Sajidan; Oetomo, Dwi; Prasetyanti, Nanik Murti; Parmin, Parmin (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
The objectives of this research was to examine the implementation of Science Integrated Learning Model in improving critical thinking skills of 11 Indonesian high school student in the excretion system and immune system. This research is a Class Action Research (CAR). Subjects were eleventh-grade students in the academic year of 2017/2018 consisted of 31 students, specifically 18 male students and 13 female students. The data was collected from students and teachers. Data collection techniques were conducted by observation, interview, and documentation study. The triangulation technique was used to verify the validity of the data. The data analysis technique employed was a qualitative descriptive analysis. The research procedure used an interrelated spiral CAR model. The experiment was conducted in two cycles, each cycle consisted of planning, action implementation, observation, and reflection. The result shows that students' critical thinking skills increased from 42.78% before research, become 54.92% in the first cycle, then 78.73% in the second cycle. It can be concluded that the implementation of the Science Integrated Learning Model can improve the critical thinking skills of 11 Indonesian high school students in the excretion system and immune system.